SAFEnet and Civil Society Dynamics in Expanding Digital Public Space in Indonesia - Pohan, Ibnu Asqori; Lumban Gaol, Ezra Maharani Batavia; Felicia Jesse Amanda (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2025)
The rapid advancement of digital technologies has fundamentally transformed the landscape of civil society advocacy, particularly in the defence of digital rights in Indonesia. This study examines the evolving role of SAFEnet (Southeast Asia Freedom of Expression Network), a prominent civil society organization committed to protecting digital freedoms. Employing a qualitative case study approach, the research explores SAFEnet’s strategic responses, structural challenges, and advocacy outcomes through comprehensive literature analysis and thematic interpretation. The findings reveal that SAFEnet has transcended its initial function as a policy watchdog, emerging as a facilitator of digital public discourse, a provider of legal assistance, and a cross-sectoral coalition builder advancing the rights to freedom of expression, data privacy, and digital justice. Its integrated advocacy model encompasses social media mobilization, digital literacy campaigns, policy engagement, and the innovative use of technology to amplify civic participation. Despite operating within a restrictive regulatory environment characterized by censorship and the criminalization of dissent, SAFEnet has demonstrated adaptive resilience and strategic innovation in expanding the digital public sphere and promoting democratic engagement. This study contributes to the discourse on digital civil society by critically mapping a localized advocacy model and by reinforcing the theoretical relevance of network society and public sphere frameworks in the context of Indonesia’s evolving digital democracy.